Citizenship and Democracy in Further and Adult Education - Hopkins, Neil.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2014)
This book addresses the questions why citizenship education is an important subject for students in further and adult education and why we need democratic colleges to support the study of citizenship education. It investigates the historical roots of further and adult education and identifies how the adoption of citizenship education in the post-compulsory sector can enrich vocational studies in further education and programmes in adult education. It is argued that democratic colleges are vital to ensure that citizenship education informs the decision-making process throughout educational institutions (and as a means of establishing fair and equal representation for important stakeholders). The author has worked in both sectors for over a decade, and uses this experience to offer a blend of educational practice and philosophical investigation. The result is a work that appeals to both teachers in further and adult education as well as academics and students interested in philosophy of education.
1. Introduction -- 2. Citizenship and Political Philosophy -- 3. Further and Adult Education: An Overview of Citizenship -- 4. The Apprenticeship Tradition in Further Education -- 5. Vocational Education: A European Perspective -- 6. The Self-Help Tradition in Adult Education -- 7. College Governance and Deliberative Democracy -- 8. Conclusion -- References -- Index.
Keywords: Education; Philosophy and social sciences; Education -- Philosophy; Lifelong learning; Adult education; Education; Lifelong Learning/Adult Education; Educational Philosophy; Philosophy of Education; Electronic books